DeRISK SE Asia Regional Legacy Workshop Report - Soksophors, Yim; Phanna, Khieng; Barlis, Angelica (2022)
This report consolidates and presents the discussion and outputs from the Regional Legacy Workshop of DeRISK SE Asia Project, convening key stakeholders from Vietnam, Cambodia, Lao PDR and Myanmar. The workshop was organized in Phnom Penh, Cambodia with support from country partners, IIRR and Ministry of Agriculture Forestry and Fisheries (MAFF).